2021
DOI: 10.1038/s41562-021-01142-4
|View full text |Cite
|
Sign up to set email alerts
|

Initial evidence of research quality of registered reports compared with the standard publishing model

Abstract: research question and the quality of the methodology, not whether the findings are positive, novel, and clean.More than 250 journals have adopted RRs since 2013 on the theorized promise of improving rigor and credibility. Initial evidence suggests that RRs are (1) effective at mitigating publication bias with a sharp increase in publishing negative results compared to the standard model 26,27 , and (2) cited as often or even more than other articles in the same journals 28 .However, there is no evidence about … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
89
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(109 citation statements)
references
References 46 publications
0
89
0
3
Order By: Relevance
“…If authors follow the accepted plan, their article is published even when their results do not support the hypotheses. The study by Soderberg et al (2021) showed that Registered Reports were assessed by experts as better in all criteria (from the rigor of methodology and results to novelty and creativity) when compared with other (non-registered) papers.…”
Section: Discussionmentioning
confidence: 99%
“…If authors follow the accepted plan, their article is published even when their results do not support the hypotheses. The study by Soderberg et al (2021) showed that Registered Reports were assessed by experts as better in all criteria (from the rigor of methodology and results to novelty and creativity) when compared with other (non-registered) papers.…”
Section: Discussionmentioning
confidence: 99%
“…For many years the typical process has been to run a study, write-up the outcome, and hope to find a home for your work in one of the myriad of publishing outlets. However, taking our own field of Psychology as an example, as highlighted in the fallout of the Reproducibility Crisis (Soderberg et al, 2021), this standard route can lead to an increase in the quantity of publications but not necessarily an increase in quality, with approximately two-thirds of replicated studies failing to show the same effect as in the original study. This would not be such an important issue if it were not for the fact that approaches to teaching are borne out of these findings; Hansford (2021), for example, highlights a variety of measures implemented in pedagogical settings.…”
Section: Improving Pedagogy Through Registered Reportsmentioning
confidence: 99%
“…Therefore, even within replications, there is an issue of transparency of methods that may affect the outcome of the study and, as such, the research we base pedagogy on exhibits the same challenges of scientific credibility as other fields highlighted in the replication crisis (Soderberg et al, 2021;Munafò et al, 2017; In turn, and if the solution is not solely via replication, then the field as a whole would benefit from approaches that allow researchers to adopt norms related to transparency of methods, and to participate in practices that improve the quality and quantity of the evidence we base our teaching approaches on (Vazire, 2018).…”
Section: Improving Pedagogy Through Registered Reportsmentioning
confidence: 99%
“…During Stage 1, the value of the research question, the rationale for the hypothesis, and the validity of the methods are assessed [1]. This allows reviewers to assist authors in improving the protocol and rationale, or to make changes that will further improve the quality of the paper [3]. As a result of peer review and revision, if the protocol is judged to be publishable, it is accepted in principle for publication, regardless of the results of experiments performed afterward.…”
Section: Introductionmentioning
confidence: 99%